2012
DOI: 10.1371/journal.pone.0049688
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Face of P300 BCIs: A Comparison of Stimulus Changes in a P300 BCI Involving Faces, Emotion, and Movement

Abstract: BackgroundOne of the most common types of brain-computer interfaces (BCIs) is called a P300 BCI, since it relies on the P300 and other event-related potentials (ERPs). In the canonical P300 BCI approach, items on a monitor flash briefly to elicit the necessary ERPs. Very recent work has shown that this approach may yield lower performance than alternate paradigms in which the items do not flash but instead change in other ways, such as moving, changing colour or changing to characters overlaid with faces.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
2
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 51 publications
3
84
2
7
Order By: Relevance
“…This implies that stimuli with higher cognitive task requirements such as facial images, are more effective than the intensified stimuli of dull characters for a P300-based BCI system. As already discussed above, previous studies have shown that faces boost BCI performance [40], [41], [43], [44]. Furthermore, familiar and famous faces have been shown to improve BCI performance even more, when compared to unknown faces [40], [41].…”
Section: Concluding Discussionmentioning
confidence: 64%
“…This implies that stimuli with higher cognitive task requirements such as facial images, are more effective than the intensified stimuli of dull characters for a P300-based BCI system. As already discussed above, previous studies have shown that faces boost BCI performance [40], [41], [43], [44]. Furthermore, familiar and famous faces have been shown to improve BCI performance even more, when compared to unknown faces [40], [41].…”
Section: Concluding Discussionmentioning
confidence: 64%
“…However, only dummy face was used in that study. It was proven that the use of a face pattern was superior to a flash pattern (Jin et al, 2012b). There was no study that showed the difference between dummy faces and human faces that were used in BCI systems.…”
Section: Introductionmentioning
confidence: 99%
“…Because the P300 is relatively easy to detect and its amplitude depends on voluntarily controlled endogenous attentional processes, it is often used as a control signal in brain-computer interfaces (BCIs; Farwell & Donchin, 1988;Jin et al, 2012;Sellers, Krusienski, McFarland, Vaughan, & Wolpaw, 2006). In P300 BCIs, different stimuli are presented sequentially.…”
Section: Introductionmentioning
confidence: 99%